GURU PAI DALAM MENINGKATKAN MOTIVASI BELAJAR SISWA DI MASA PANDEMI COVID-19 (Studi Kasus: SMKN 3 Kota Bekasi) - Zulfatul Musyarofa; Yayat Suharyat (Turats, 2021)
During the Covid-19 pandemic, the learning system was shifted to online learning methods.Changes in the learning process cause a decrease in students’ learning motivation. Motivation tolearn greatly affects the success that becomes an achievement in educational goals. To achievethis goal, of course, good cooperation between teachers and students is needed. In this case, theteacher as a student motivator is required to provide efforts to foster student learning motivation,especially in learning carried out during the pandemic.The focus of the problem in this study is theefforts of PAI teachers in increasing student learning motivation during the Covid-19 pandemic andthe obstacles faced by PAI teachers in increasing student learning motivation. The aim is to findout the efforts of PAI teachers in increasing student learning motivation as well as the obstaclesfaced by PAI teachers in increasing student learning motivation during the Covid-19 pandemic. Fieldresearch that is descriptive naturalistic. Data collection techniques using interviews, observation, anddocumentation. Based on the results of the study, it was concluded that:First,PAI teachers’ efforts inincreasing students’ learning motivation are clarifying the goals to be achieved, generating studentinterest in learning, creating a pleasant atmosphere, providing rewards, creating competition andcooperation for students.In the efforts of teachers to motivate students during the Covid-19 pandemic,teachers must be even more extravagant compared to motivating students when they are offline. If it isa percentage, 70% of teachers motivate students when they are offline and 95% of teachers motivatestudents when they are online. Second,The obstacles faced in increasing student learning motivationare: students do not have internet quota, network connections are lost, student learning interest isreduced, interaction is limited, material delivery is not optimal.